2016
DOI: 10.1080/17453674.2016.1193663
|View full text |Cite
|
Sign up to set email alerts
|

Total joint replacement: A multiple risk factor analysis of physical activity level 1–2 years postoperatively

Abstract: Background and purpose — The effect of total joint arthroplasty (TJA) on physical activity is not fully understood. We investigated the change in physical activity after TJA and patient factors associated with change.Patients and methods — Using a total joint replacement registry, primary total hip arthroplasty (THA) patients (n = 5,678) and knee arthroplasty (TKA) patients (n = 11,084) between January 1, 2010 and December 31, 2012 were identified. Median age at THA was 68 and median age at TKA was 67. Change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…Consequently, their preoperative PA levels may still have been relatively high and therefore a significant postoperative PA increase may have been unlikely [9]. Finally, high body mass index (BMI) is negatively associated with PA behavior in patients undergoing total joint arthroplasty [26,27]. In KA, Twiggs et al [28] found that obese patients reached a mean of 4819 steps 6 weeks postoperatively, compared to 7151 steps for overweight patients and 8022 steps for healthy weight patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, their preoperative PA levels may still have been relatively high and therefore a significant postoperative PA increase may have been unlikely [9]. Finally, high body mass index (BMI) is negatively associated with PA behavior in patients undergoing total joint arthroplasty [26,27]. In KA, Twiggs et al [28] found that obese patients reached a mean of 4819 steps 6 weeks postoperatively, compared to 7151 steps for overweight patients and 8022 steps for healthy weight patients.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding possible solutions to further increase PA after KA, in order for more patients to meet health-enhancing PA guidelines, several authors have suggested a need for improved and individually tailored rehabilitation strategies [27,29]. The patienttailored GAS rehabilitation of our intervention group focused specifically on achieving activities that our individual patients wished to perform better.…”
Section: Discussionmentioning
confidence: 99%
“…Toogood et al also showed that BMI greater or less than 30 kg/m 2 had no influence on objective activity level [20]. In contrast to these results, self-reported physical activity at 1–2 years postoperatively after THA and TKA was lower depending on BMI, female sex, and specific comorbidities [22]. …”
Section: Discussionmentioning
confidence: 99%
“…Types of activity and number of studies in which they were reported. Ergometer cycling 1 [7] 2 [7,8] Intensive physiotherapy 3 [8][9][10] Fast-track treatment 2 [11,12] 1 [11] Walking skill training 1 [13] Arm/upper body exercise 1 [14] Leisure activity (MET-hours/week, minutes/week) 2 [15,16] 4 [15][16][17][18] Winter sports (alpine skiing, cross-country skiing) 1 [19] 3 [18,20,21] Summer sports (trekking, hiking, biking, swimming) 1 [19] 3 [18,20,21] High-impact physical activity (baseball, gymnastics, hockey, basketball, martial arts, football, tennis) 2 [18,20] Low-impact physical activity (aquafit, golf, cycling, swimming) 2 [18,20] 3.…”
Section: Total Hip Arthroplastymentioning
confidence: 99%